Numerical study on coal gasification in supercritical water fluidized bed and exploration of complete gasification under mild temperature conditions. (12th October 2019) - Fan, Chao; Guo, Simao; Jin, Hui
Highlights: Coal gasification in supercritical water fluidized bed was simulated. Multi-field distribution in the reactor was revealed. K2 CO3 can obviously reduce the required gasification temperature. Extension of reactor length can promote gasification results. A scheme for complete gasification of lignite under mild condition was proposed. Abstract: Supercritical water fluidized bed is a promising reactor for the industrial application of the technology of supercritical water gasification of coal. In this work, a numerical model of lignite gasification in SCWFB considering flow, heat transfer and gasification reaction was established, and the Euler-Lagrange method and RNG k - ε model were used. Through this model, the multi-field distribution characteristics and developing rules were studied under wide temperature range. A low-temperature zone with uneven circumferential temperature distribution was found below the feed inlet, and the average residence time decreased with the increase of reactor temperature. Steam reforming of solid residual carbon was the bottleneck of complete gasification, and the alkali salt catalyst can accelerate its reaction rate and cause the reaction zone to move to the lower fluidization section. Besides, the simulated results show that the extension of the reactor length was an effective means to improve the carbon gasification efficiency, and the increase of the feed inlet height can avoid the blockage of distributor. Based on both the catalyst addition and reactor structure optimization, a scheme was proposed where the complete gasification of lignite at 750 °C was achieved with H2 promotion promoted.